Redeeming love : a novel - Rivers, Francine, 1947- (Multnomah, 2005)
Sold into prostitution as an orphan, Angel has never believed in love. Then Michael Hosea pursues her, showers her with unconditional love, and marries her. Through his caring, Michael slowly melts Angel's icy heart.